A friend for Henry - Bailey, Jenn, 1965- (Chronicle Books LLC, 2019)
"Henry would like to find a friend at school, but for a boy on the autism spectrum, making friends can be difficult, as his efforts are sometimes misinterpreted, or things just go wrong--but Henry keeps trying, and in the end he finds a friend he can play with." --